IMPORTANCE OF AGRICULTURAL PRODUCTS IN THE ECONOMIC SECTOR OF UZBEKISTAN (Academicia Globe: Inderscience Research, 2022)
Nowadays, the most effective way to raise and develop agricultural products is of a strategic nature, the real guarantee of agricultural producers' confidence in their own competitive positions in the world market, the means by which enterprises adapt to changes in the external environment, new jobs are created, and, accordingly, a necessary condition for the development of rural areas are innovations. Innovations in agriculture are, first of all, new varieties of plants, breeds of animals and poultry crosses, new fertilizers and means of protection to grow on and animals, modern technology, new methods of prevention and treatment of animals, technologies, forms of organization and financing of production, approaches to training, etc.